(Des) caminhos dos concursos de arquitetura no Ceará (1969-2017) - Cattony, Luiz Mattozo (2019)
In Brazil, architectural design contests have been held since the mid-nineteenth century. Although they have been taking place in the country for over 150 years and the legislation defines the preference for this project hiring format, only 373 bids were held in Brazil between 1857 and 2010. The choice of the object of study related to architecture and urbanism competitions Ceará is due to the relevance of this hiring model to society in general, in which architects, public and private clients and users are involved, as well as important works that were built and constitute an important cultural collection for the State. The period of the research is between 1969 and 2017, where it was possible to identify the holding of 21 public design contests in Ceará, of which 15 were architectural and six urban planning. Given the bibliography on the competitions, it is found that information about events in Ceará are scattered and without any systematization and analysis. The contribution of this research to the theme is to document the architectural competitions in Ceará and systematize the data allowing an analysis of the efficiency of the events and indicating new ways for its practice. Thus, the general objective of this research is to understand and analyze to what extent the contest is a democratic instrument in the contracting of architecture and urbanism in Ceará, emphasizing the social and cultural importance of this form of contracting. Therefore, it presents a historical perspective of architecture competitions in Brazil, exposing a panorama of the events and their evolution within a historical-social context. Along with this panorama of events is presented the evolution of legislation on public procurement of projects related to competitions and its regulations, as well as a survey on writing and research of the theme within dissertations, theses, articles and journals. Following is a survey of the competitions held in the state of Ceará considering the social and political context of the states, the agents involved and the role of architects within these processes. Finally, we present an analysis and reflection on the competitions held in Ceará, within parameters of when they were efficient, when they were not and a third point is when there was no competition for a building of public relevance. The analysis allows reflecting and understanding the existing contradictions in the project selection and contracting process.